Customers' reaction towards retail strategy of Carrefour house brand products / Ernieda Mohd Nor - Mohd Nor, Ernieda (Faculty of Business and Management, 2006)
This research focused on customers' reaction towards the retail strategy of Carrefour house brand products. The main objective of this research is to identify which one of the retail strategies of Carrefour house brand products needs to be improved and recommendation for suitable retail strategies for the better growth in the future. The main sources of information are gathered and analyzed from the 100 questionnaires prepared and distributed to the Carrefour customers in Subang Jaya and Sri Petaling respectively 50 respondent for each area. The target customers for this research were customers that made a purchase in Carrefour. Systematic random sampling method was used in this survey. Questionnaire has been divided by 7 sections which are Section A to Section G. The questionnaire consists of multiple choices, Iikert scale and several numbers of open-ended questions. The analysis includes a frequency distribution for variable produced, cumulative percentages for the entire value associated with the variable. The answers collected were also determined by examining mean and cross-tabulation. The conclusion of this research was the outcome from the survey analysis and findings. The research shows that retail strategy of Carrefour house brand products is still need to be improved in order to attract more customers and at the same time easily to compete with other competitors.